6ax+30b^2y^2-12b^2x-15ay^2 =6ax-15ay^2+30b^2y^2-12b^2x =3a(2x-5y^2)+6b^2(5y^2-2x) =[2x-5y^2][3a-6b^2](没化简也算不对)

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 13:17:18
6ax+30b^2y^2-12b^2x-15ay^2=6ax-15ay^2+30b^2y^2-12b^2x=3a(2x-5y^2)+6b^2(5y^2-2x)=[2x-5y^2][3a-6b^2](没

6ax+30b^2y^2-12b^2x-15ay^2 =6ax-15ay^2+30b^2y^2-12b^2x =3a(2x-5y^2)+6b^2(5y^2-2x) =[2x-5y^2][3a-6b^2](没化简也算不对)
6ax+30b^2y^2-12b^2x-15ay^2
=6ax-15ay^2+30b^2y^2-12b^2x
=3a(2x-5y^2)+6b^2(5y^2-2x)
=[2x-5y^2][3a-6b^2]
(没化简也算不对)

6ax+30b^2y^2-12b^2x-15ay^2 =6ax-15ay^2+30b^2y^2-12b^2x =3a(2x-5y^2)+6b^2(5y^2-2x) =[2x-5y^2][3a-6b^2](没化简也算不对)
6ax+30b^2y^2-12b^2x-15ay^2
=6ax-15ay^2+30b^2y^2-12b^2x
=3a(2x-5y^2)+6b^2(5y^2-2x)
=3a(2x-5y^2)-6b^2(2x-5y^2)
=[2x-5y^2][3a-6b^2]
=3[2x-5y^2][a-2b^2]

=[2x-5y^2][3a+6b^2]
最后一步~~

dui